Conserving our environment use and reuse : the pollution crisis (Coronet MTI Film & Video, 1972)
The ecological system of a fishbowl depicts in miniature the ecology of the earth, demonstrating the interdependence of plant and animal organisms, and the harmful effects of man's interference with the environment.